Virtual Reality Practices in Special Education - ERBAŞ, DİLEK; ÖZDEMİR, ONUR (ANKARA UNIV, FAC EDUCATIONAL SCIENCES, 2019)
Virtual reality refers to interactive three-dimensional computer-generated simulations which are experienced multisensory. Virtual reality practises while has been discussed in the computer sciences since 1970's, has become more accessible to the public with the advances in technology in recent years. Special education field also benefits from these current developments, as the number of virtual learning environments developed for the persons with special needs increase each passing day. Solutions responding to different kind of needs for the individuals with special needs are developed with virtual learning environments. These applications can be used for the instruction of various academic, social, daily life, communication skills or supporting skills or for various types of supports. In the literature there are several research studies evaluating virtual learning environments developed for different kind of special needs groups including

autism spectrum disorder, intellectual disabilities, physical disabilities, hearing impairments. Recent study discusses the opinions on virtual learning environments on the basis of literature.
Keywords: Technology; virtual reality; virtual reality environments; virtual reality applications; individuls with special needs; LEARNING-ENVIRONMENT; CHILDREN; PEOPLE; AUTISM; STUDENTS; DISABILITIES; ADULTS; SKILLS; REHABILITATION; COMMUNICATION